Increased serum chemerin levels associated with carotid intima-media thickness - Caner Feyzi DEMİR; İklimya Nimet ATAŞ; Ferhat BALGETİR; Hakan ARTAŞ; Murat GÖNEN; Süleyman AYDIN (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Elevated levels of chemerin can predict future ischemic cerebrovascular disease. Although chemerin is thought to play a role in atherosclerotic inflammation, whether circulating chemerin levels are associated with the severity of atherosclerosis remains to be determined. Objectives: Through the use of carotid Doppler ultrasonography, our aim in this study was to investigate the relationships of serum chemerin levels with carotid intima-media thickness (CIMT) as an indicator of generalized atherosclerosis. Methods: This study compared 40 patients with ischemic stroke and 40 healthy subjects. Measurements were made at end-diastole using color Doppler ultrasonography (CDUS) after a 5-min rest interval in a quiet and dark room. CIMT was defined as the distance between the innermost edge of the luminal echo to the innermost edge of the media/adventitia echo. CIMT was measured in the posterior wall of both common carotid arteries within 1 cm proximally to the bulbus. Three measurements were made on both sides and the average measurement was taken as the CIMT. Serum chemerin levels were determined in all patients and healthy subjects. Results: Serum chemerin levels were significantly higher in the patient group than in the control group (p=0.004). Serum chemerin levels were positively correlated with CIMT (p<0.05). There was a significant difference between the groups with regard to CIMT (p<0.001). Conclusion: Elevated serum chemerin levels appear to be associated with CIMT, thus suggesting that a link exists between chemerin and atherosclerotic ischemic cerebrovascular disease.